Can we synthesise a dense bundle of quasi one-dimensional metallic wires? - Edwards, P; Anderson, P; Woodall, L; Porch, A; Armstrong, A (1996)
In two timely publications, Kelly [1,2] has recently highlighted the poor prospects for practical quasi one-dimensional electronic devices in the context of existing fabrication technologies. One of the proposed radical alternatives, viewed from a long-term prospective, relates to the concept of "crystal engineering" in the fabrication of such devices. Here, inorganic materials will themselves be engineered totally on the nanometer scale, with the ultimate goal being the deliberate manufacture of electronic band structures fully tailored to the particular device application. In this context, metal-loaded zeolites have recently been identified [2] as potential candidates in the search for a dense bundle of quasi one-dimensional wires. This intriguing proposal, emanating from a major figure in the science and application of electronic devices, dovetails with our own interest in the possibility of a compositionally-induced insulator-to-metal transition in alkali metal-loaded zeolites. In recent work we have highlighted the possibility that through the controlled introduction of alkali metals into the one-dimensional channels of zeolite L, it may be feasible to engineer genuine charge (electron) transport along the channels. Our goal is to produce totally engineered materials comprising a precise mesoscopic assembly of ultrafine atomic-scale conducting wires embedded within an insulating aluminosilicate host framework. In this paper, we report preliminary conductivity measurements on a series of potassium-loaded zeolite L samples. We examine the results of these physical measurements as a function of potassium composition as they approach the insulator-metal transition; the nature, origin and location of this electronic phase transition will underpin the search for such a dense bundle of metallic quasi one-dimensional wires.